Implementasi Kurikulum Merdeka dalam Perspektif Manajemen Pendidikan Islam di SMA Negeri 2 Ranah Batahan - Andrian, Yogi; Rifa'i, Muhammad (Universitas Negeri Malang, 2024)
Abstract: The curriculum plays a vital role in educational institutions as it determines the direction, content, and processes of learning, ultimately influencing the type and quality of graduates. Within the education system, the curriculum serves as the main framework guiding the achievement of national education goals. This paper aims to understand the concept of Merdeka Belajar (Freedom to Learn) for students. The curriculum holds a crucial role in shaping the educational journey by defining its direction, content, and processes, which in turn impacts the type and quality of graduates produced. This study employs a literature review method with a qualitative approach. The findings reveal that the Merdeka Belajar concept restores the role of educational literacy to its intended purpose as a strategic moment in achieving national education objectives. Through Merdeka Belajar, students’ literacy in religious spirituality, self-control, personality, intelligence, moral character, and skills can be enhanced, ultimately contributing to the recovery and improvement of education quality in Indonesia. In other words, Merdeka Belajar provides space for students to grow holistically, in alignment with their individual potential and interests. The implementation of Merdeka Belajar is seen as an important effort to support the recovery and enhancement of educational quality in Indonesia, especially in addressing global challenges and local needs. This approach is expected to produce graduates who are not only intellectually capable but also strong in character and equipped with relevant life skills. Therefore, Merdeka Belajar is believed to be a solid foundation for realizing more inclusive and meaningful education. Keywords: Independent Learning Curriculum, Islamic Education Management Abstrak: Kurikulum memiliki peran yang sangat penting dalam lembaga pendidikan karena menentukan arah, isi, dan proses pembelajaran yang pada akhirnya memengaruhi jenis dan mutu lulusan. Dalam sistem pendidikan, kurikulum menjadi kerangka utama yang mengarahkan pencapaian tujuan pendidikan nasional. Tujuan penulisan ini adalah untuk memahami kurikulum merdeka dalam belajar bagi peserta didik. Kurikulum memegang peranan penting dalam lembaga pendidikan karena menentukan arah, isi dan proses pendidikan yang pada akhirnya berpengaruh terhadap jenis dan mutu lulusan. Penelitian ini menggunakan metode studi pustaka dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa konsep Merdeka Belajar mengembalikan peran literasi pendidikan sesuai dengan tujuannya sebagai momen strategis dalam mencapai tujuan Pendidikan Nasional. Dengan Merdeka Belajar, literasi peserta didik dalam spiritualitas keagamaan, pengendalian diri, kepribadian, kecerdasan, akhlak mulia dan keterampilan dapat ditingkatkan yang pada akhirnya akan mendukung pemulihan mutu pendidikan di Indonesia. Dengan kata lain, Merdeka Belajar memberikan ruang bagi siswa untuk berkembang secara holistik, sesuai dengan potensi dan minat mereka masing-masing. Implementasi Merdeka Belajar juga dipandang sebagai upaya penting dalam mendukung pemulihan dan peningkatan mutu pendidikan di Indonesia, terutama dalam menghadapi tantangan global dan kebutuhan lokal. Pendekatan ini diharapkan mampu membentuk lulusan yang tidak hanya cerdas secara intelektual, tetapi juga berkarakter kuat dan memiliki keterampilan hidup yang relevan. Dengan demikian, Merdeka Belajar diyakini dapat menjadi fondasi yang kokoh untuk mewujudkan pendidikan yang lebih inklusif dan bermakna. Kata Kunci: Kurikulum Belajar Mandiri, Manajemen Pendidikan Islam